The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3892/ijo_00000724
|View full text |Cite
|
Sign up to set email alerts
|

Lithium induces mortality in medulloblastoma cell lines

Abstract: Abstract. Lithium is the main therapeutic agent for the treatment of bipolar disorders but nerve cells are not the sole target of this drug. Indeed, lithium has been reported to target numerous cell types and to affect cell proliferation, differentiation and death. Lithium targets a variety of enzymes among which there is GSK-3ß and a number of cell responses elicited by lithium are mediated by the Wnt pathway that is involved in medulloblastoma (MB) pathogenesis. We studied the in vitro effects of lithium on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Phosphorylation of GSK3β at serine 9 is inhibitory phosphorylation of GSK3β kinase activity and is found to be upregulated once the β-catenin signaling is activated. 57,73 Our results confirm that phospho GSK3β serine 9 and c-Myc protein levels are downregulated in the nucleus after ALDH2 inhibition. However, we found that the total nuclear β-catenin protein level, indicative of Wnt/β-catenin signaling, has not decreased after ALDH2 inhibition by both daidzein and CVT-10216.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Phosphorylation of GSK3β at serine 9 is inhibitory phosphorylation of GSK3β kinase activity and is found to be upregulated once the β-catenin signaling is activated. 57,73 Our results confirm that phospho GSK3β serine 9 and c-Myc protein levels are downregulated in the nucleus after ALDH2 inhibition. However, we found that the total nuclear β-catenin protein level, indicative of Wnt/β-catenin signaling, has not decreased after ALDH2 inhibition by both daidzein and CVT-10216.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, phosphorylation of GSK3β at serine 9 significantly decreased after ALDH2 inhibition by both daidzein and CVT‐10216. Phosphorylation of GSK3β at serine 9 is inhibitory phosphorylation of GSK3β kinase activity and is found to be upregulated once the β‐catenin signaling is activated 57,73 . Our results confirm that phospho GSK3β serine 9 and c‐Myc protein levels are downregulated in the nucleus after ALDH2 inhibition.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, a potential effect on p57 at prolonged lithium therapeutic dosage might not be ruled out. Second, our study employs concentrations of the drug that have been frequently used in investigations evaluating lithium as an anti-proliferative agent in the treatment of numerous cancers, including glioma [44], colorectal cancer [45], medulloblastoma [46], hepatocellular carcinoma [47], and other tumors [48]. Although the dosages employed in these studies were clearly toxic, the development of delivery strategies specifically targeting cancer cells is conceivable.…”
Section: Critical Assessment On Lithium-employed Concentrations and Dmentioning
confidence: 99%